Efficacy and Effectiveness of Physical Therapy in Enhancing Postural Control in Children With Cerebral Palsy - Susan R. Harris; Lori Roxborough (Neural Plasticity)
The purpose of this article was to conduct a systematic review of studies that examined the efficacy and effectiveness of postural control intervention strategies for children with CP. Only physical therapy interventions were included, e.g. adaptive seating devices, ankle foot orthoses, neurodevelopmental treatment. A multifaceted search strategy was employed to identify all potential studies published between 1990 and 2004. The search strategy included electronic databases, reference list scanning, author and citation tracking of relevant studies, and hand searching of pediatric physical therapy journals and conference proceedings. Twelve studies (1991–2004), comprising ten group design studies and two single subject studies, met our inclusion criteria. A variety of age ranges and severity of children with cerebral palsy (n = 132) participated in the studies. The study quality scores ranged from 2 to 7 (total possible range of 0 to 7) with a median score of 5.5 and a mode of 6. As was true in an earlier systematic review on adaptive seating, most of the 12 ‘experimental’ studies published since 1990 that were aimed at evaluating the effectiveness of postural control strategies provided lower levels of evidence, i.e. Sackett Levels III to V. Additional studies with stronger designs are needed to establish that postural control interventions for children with CP are effective.